STUDY OF HISTOPATHOLOGICAL CHANGES INDUCED BY ENDOSULFAN IN KIDNEY OF ALBINO RATS - Khan, Sabiha (Journal of Drug Delivery and Therapeutics, 2014)
Endosulfan, a neurotoxic organochlorine insecticide and cypermethrin, a synthetic pyrethroid insecticide used to control pests in domestic, industrial, and agricultural situations.Â An effective dose (1/3rd , 1/6th of 0.28 ppm/kg-1 Â LD50) of endosulfan was injected to 4, 5 and 6 week of albino rats and its exposure was studied on histopathology of kidney after 15, 30 and 45 days of exposure. The Â histopathological changes in renal tissue of rats exposed to endosulfan by interdermal injection showed pronounced changes in the structure of renal corpuscles and caused renal necrosis. The examination revealed nephrotoxic effects on endosulfan treated rats.Â The effect of this pesticide on oxidative stress and its biodegradation were also explained. This review will be useful for the researchers working in the field of pesticides and will create an awareness regarding its hazardous effect. Keywords: Endosulfan, histopathology, intradermal, nephrotoxic necrosis.